An empirical analysis of corporate governance structures and voluntary corporate disclosure in volatile capital markets: the Egyptian experience. (27th December 2010) - Samaha, Khaled; Dahawy, Khaled
This paper examines the level and determinants (i.e. ownership structure, board composition and audit committee presence) of voluntary corporate disclosure in the annual reports of the largest 100 companies listed on the Egyptian stock exchange (EGX). Our results indicate that overall voluntary disclosure was low at just 13.43% with a large variation range. This score places Egypt at a lower level than other emerging capital markets (e.g. Singapore, Hong Kong and Malaysia). The variances of these results support the need for individual country level studies and comparative analysis. Multivariate results show audit committee presence as the most significant variable influencing voluntary disclosure. Also, companies with a higher ratio of independent non-executive directors have a higher extent of voluntary disclosure. It was also evidenced that voluntary disclosure increases with decreases in block-holder ownership. Results show that two other ownership aspects – managerial and government – are not related to voluntary disclosure. Finally, the analysis shows profitability and internationality significantly impact voluntary disclosure. On the other side, that number of shareholders, type of auditor, size, liquidity, leverage and industry type of the firm do not affect the extent of voluntary disclosure.